2010
DOI: 10.4314/njps.v23i1-2.54919
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemic and hypolipidaemic effects of the aqueous leaf extract of murraya koenigii in normal and alloxan – diabetic rats

Abstract: Summary:The hypoglycaemic effect of aqueous leaf extract of Murraya koenigii was studied in normal and alloxan-induced diabetic rats. The extract was administered orally at 100 mg/Kg, 150 mg/Kg and 200 mg/Kg bodyweight each to respective groups of animals (Groups I, II and III) for seven days. Group IV received normal saline and served as control for the normal rats. For the alloxan-induced diabetic rats, the same dosage pattern was administered to three groups of rats for seven days (Groups V, VI and VII) whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 9 publications
2
16
1
2
Order By: Relevance
“…This has probably contributed to the widespread use of the plant as a spice for food flavouring, in many local cuisines in Malaysia. Hence, the choice of our graded dose levels for the extract was as a result of the high margin of safety from this test which also agreed with the study reported earlier by Lawal et al (2008). Our result show decreased plasma antioxidant capacity (PAC), and increased glutathione peroxidase (GPx) levels in diabetic controls compared to normal controls (Figs.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This has probably contributed to the widespread use of the plant as a spice for food flavouring, in many local cuisines in Malaysia. Hence, the choice of our graded dose levels for the extract was as a result of the high margin of safety from this test which also agreed with the study reported earlier by Lawal et al (2008). Our result show decreased plasma antioxidant capacity (PAC), and increased glutathione peroxidase (GPx) levels in diabetic controls compared to normal controls (Figs.…”
Section: Discussionsupporting
confidence: 94%
“…Variations in dose-dependent response effect, and in comparison to normal controls, could probably be attributed to the diversifying nature of indigenous plants as reported earlier. Lawal et al (2008) reported higher glucose lowering effect by AQ extract of the leaves of Murraya koenigii in alloxan-treated diabetic rats compared to normoglycaemic animals. Similarly, dose-independent response effect on blood glucose levels was observed with Vinca rosea (Chattopadhyay et al, 1991), Aegle marmelose (Rao et al, 1995) and Cinnamomum tamala (Sharma et al, 1996).…”
Section: Discussionmentioning
confidence: 96%
“…The feeding of M. koenigii leaves (for 60 days) to normal rats has been shown to produce hypoglycemic effect along with an increase in hepatic glycogen levels [56]. Other studies have also revealed the hypoglycemic activity of aqueous leaf extract of M. koenigii in alloxan-induced diabetic rats and dogs [35,57]. P. nigrum has been shown to lower glucose levels due to potent pancreatic α-amylase inhibitory activity leading to a reduction in starch hydrolysis and, eventually, to lowered glucose levels [33].…”
Section: Discussionmentioning
confidence: 98%
“…Its leaves are used as an herb in Ayurvedic medicine and commonly used as spice in Indian kitchens. Earlier studies have demonstrated the antidiabetic and antioxidant potential of its leaf-derived extracts [34,35]. Crude extracts of P. nigrum and M. koenigii were shown to inhibit aldose reductase activity [13].…”
Section: Introductionmentioning
confidence: 99%
“…The leaves showed potent antioxidant activity both in vitro and in vivo (Tachibana et al 2003). Hypoglycemic, anti-hyperlipidemic activities and safety of M. koenigii were demonstrated earlier (Lawal et al 2008).…”
mentioning
confidence: 94%